Banana peels: a new carbon source for bioprotein production by utilizing phanerochaete chrysosporium and candida utilis - Jamal, Parveen; Saheed, Olorunnisola Kola; Alam, Md. Zahangir (2012)
Bioprotein production from underutilized fruit peels is one of the most promising breakthroughs of biotechnological innovations. This research was carried out to increase the availability of high quality affordable proteins by fermentation of Banana peels (BP), which is a lignocellulosic waste generated by many food industries. Pretreatment of BP at different temperatures (20OC, 40OC, 60OC, 80OC and 100OC) was done to reduce the amount of saponin content. Forty percent reduction in saponin was observed at 1000C (from 9.5mg/g to 5.7mg/g). Solid state bioconversion was done by sequential mixed culture of Phanerochaete chrysosporium (PC) and Candida utilis (CU) and 88.93mg/g of bio-protein was produced. Further increment in bioprotein content from 88.93 to 111.78mg/g was achieved after screening of media compositions by using Placket Burman Design. Experimental results showed that BP, KH2PO4, FeSO4.7H2O, wheat flour and sucrose contributed at low level while urea, peptone, K2HPO4, KCl, NH4H2PO4, and MgS04.7H2O contributed at their high levels. Total soluble sugar (TOS), total reducing sugar (TRS) and total carbohydrate (TC) contents obtained were also high. This study showed a promising result with improved protein for selected potential substrate at optimum level of selected media parameters, which were 5% sucrose, 0.6% NH4H2PO4, 0.4% KCl and 0.5% MgS04.7H2O. Bioprotein from local agro-waste can be a good source of supplement and additive in the animal feed as well as additives in the chemical and pharmaceutical products.